Can environmental transformational leadership shape organizational citizenship behavior toward the environment in Indonesia? - Wulandaru, Diah Retno; Robani, Anidah Binti; Putri, Zaqiah Vivi (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
This research examines the influence of environmental transformational leadership on organizational citizenship behavior toward the environment. In testing this relationship, other aspects were involved, including green human resources management, a moderating variable, and green employee empowerment, a mediating variable. To achieve their environmental goals, company employees must care about the environment, however motivating them is challenging. Research into environmental transformational leadership and green human resources management is needed in Indonesia. Research there focuses on the impact of companies’ environmentally friendly practices, seen from an external perspective. This study’s data came from an online survey of Indonesian company employees. This was processed using SmartPLS. The results show environmental transformational leadership positively influences organizational citizenship behavior toward the environment, and green employee empowerment. Green employee empowerment partially mediates the relationship between green human resources management and organizational citizenship behavior toward the environment. Green human resources management is a moderator variable in the relationship between environmental transformational leadership and green employee empowerment. Companies must have environmental transformational leadership, green employee empowerment, and green human resources management to achieve green goals. Companies must pay attention to those aspects, so their employees will show organizational citizenship behavior toward the environment to support the company’s success.